2014
DOI: 10.1063/1.4867035
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the volume of single cells continuously using a microfluidic pressure-driven trap with media exchange

Abstract: We demonstrate a microfluidic device capable of tracking the volume of individual cells by integrating an on-chip volume sensor with pressure-activated cell trapping capabilities. The device creates a dynamic trap by operating in feedback; a cell is periodically redirected back and forth through a microfluidic volume sensor (Coulter principle). Sieve valves are positioned on both ends of the sensing channel, creating a physical barrier which enables media to be quickly exchanged while keeping a cell firmly in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“… 2014 ; Riordon et al. 2014 ; Khalili and Ahmad 2015 ). Many trapping structures restrict cell growth to a monolayer in one focal plane for optical analysis by matching channel heights and dimensions of microbial cells (Gruenberger et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 2014 ; Riordon et al. 2014 ; Khalili and Ahmad 2015 ). Many trapping structures restrict cell growth to a monolayer in one focal plane for optical analysis by matching channel heights and dimensions of microbial cells (Gruenberger et al.…”
Section: Introductionmentioning
confidence: 99%
“… 2014 ; Riordon et al. 2014 ). Here we will focus on studies that retain single microbes in microstructured habitats for controlled perturbation experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prior study reported an electrical impedance method to measure single-cell volume changes using an on-chip electrical-impedance volume sensor with pressure-activated cell trapping capabilities. 22 Such an approach may be adaptable to enteroid volume measurements as an alternative to the optical approach used here.…”
Section: Enteroid Swelling Measurementsmentioning
confidence: 99%
“…When a high pressure is applied to one channel, the other one will be compressed, restricting flow. This technology has been developed as a practical way to obtain microfluidic large‐scale integration in the design and fabrication of biosensors …”
mentioning
confidence: 99%